2016
DOI: 10.1515/ijamh-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Immaturity in puberty and negative attitudes toward reproductive health among Indonesian adolescents

Abstract: Immaturity and factors that influence negative attitudes toward RH should be explored during puberty. Improving knowledge about RH may help to prevent negative attitudes toward RH, especially for girls in urban areas and boys with smoking habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
2
14
0
6
Order By: Relevance
“…In contrast, among girls, it was not clear whether access to information on development was related to active RH behavior as mediated by attitudes to RH or vice versa. This findings are similar to those of previous studies reporting that access to information [25] and pubertal development [33] were related to attitudes regarding gender and norms. This may be explained by the availability of resources for the development of adolescent health, and these findings suggest the need to provide health education about the dangers of smoking during adolescent development to minimize risky behavior and encourage positive, balanced attitudes regarding gender and RH norms during puberty based on the social and cultural context of Indonesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, among girls, it was not clear whether access to information on development was related to active RH behavior as mediated by attitudes to RH or vice versa. This findings are similar to those of previous studies reporting that access to information [25] and pubertal development [33] were related to attitudes regarding gender and norms. This may be explained by the availability of resources for the development of adolescent health, and these findings suggest the need to provide health education about the dangers of smoking during adolescent development to minimize risky behavior and encourage positive, balanced attitudes regarding gender and RH norms during puberty based on the social and cultural context of Indonesia.…”
Section: Discussionsupporting
confidence: 92%
“…Among boys, it was unclear whether current smoking may have been related to active RH behavior based on access to information on development or vice versa. These findings are similar to those of previous studies that found that smoking and information sources [20] were associated with RH [33]. In contrast, among girls, it was not clear whether access to information on development was related to active RH behavior as mediated by attitudes to RH or vice versa.…”
Section: Discussionsupporting
confidence: 87%
“…The ARH short film which is friendly with local wisdom contains ARH material, including: (1) what is adolescent reproductive health; (2) why physical changes occur when entering puberty; (3) why teenagers can menstruate and have wet dreams; (4) why adolescents often change their emotions quickly; (5) what is pregnancy; (6) what is a sexually transmitted disease; (7) what is HIV / AIDS; (8) how does LGBT occur; (9) how to maintain the cleanliness of the reproductive organs; and (10) how the juvenile life is safely accomplished during puberty. 8,20,21 The material in this short film is played by middle school students and is harmonized with the local wisdom culture according to the local social culture.…”
Section: Discussionmentioning
confidence: 99%
“…5 Meanwhile, the prevalence of the actual reproductive behavior of adolescents in the Jember Regency is 50.6%, 1 negative response during puberty in 39.0%, and immaturity during adolescent development in 20.3%. 6 This situation relates to the lack of ARH education both in families and schools because the discussion of ARH problems is considered taboo in most families and communities and there is no in-depth knowledge of reproduction problems in adolescents. 7 This challenging condition shows the magnitude of the ARH problem among adolescents who need better role models from their family, community, and school.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with high reproductive health knowledge exhibit lower negative attitudes toward reproductive health. High knowledge of reproductive health reduces negative attitudes toward reproductive health in both boys and girls [12]. A good attitude will be followed by a positive activity in maintaining reproductive health [13].…”
Section: The Data Of Questionnaires Inmentioning
confidence: 99%